De-centrality of ASEAN Law to Address US-China Rivalry in the South China Sea - Basir, Salawati Mat; Abd Aziz, Saidatul Nadia (Indonesian Journal of International Law, 2024)
Evolving Southeast Asian geopolitics offer opportunities and risks. Central to the global East-West sea route of communication and rich in land and sea resources, this region has been a geopolitical hub since ancient times. The key question is whether China's strategic actions weaken US-ASEAN relations and has an impact on regional powers. This highlights the Association of Southeast Asian Nations’ (ASEAN) importance in regional stability. This study employs qualitative research that collected data through descriptive, analytical, and case studies. ASEAN is facing challenges in effectively handling the rivalry in the Indo-Pacific area. It also has the capability to manage uncertainty within the area. Nevertheless, the “power dilemma”, particularly when significant powers want to alter the circumstances, is unavoidable. The South China Sea Arbitration altered the dynamics of territorial sovereignty. Failure to resolve the territorial dispute may jeopardize the cohesion of ASEAN and have repercussions for all its member states. ASEAN law or legal mechanism, namely ARF, ADMM, Declaration of Conduct, Code of Conduct and UNCLOS faces challenges due to a lack of coherence and a central guiding principle. It is inevitable that influential forces will meddle in regional affairs. These findings imply that ASEAN's law role in integrating Southeast Asian nations and establishing positive international cooperation and strategic partnerships is vital for successfully balancing disruptive forces. ASEAN deploys hedging and enmeshment methods to ensure dynamic alignment possibilities and make strategic adjustments easier when opposing big powers maneuver. Relevant analysis strongly suggests that ASEAN, a regional stability instrument, can influence Sino-US competitiveness.